Law, State and Telecommunications: The Broadband Gravitational Force - Board, Editorial (Law, State and Telecommunications Review, 2011)
This text introduces the Law, State, and Telecommunications Review, addressing, by way of an overview, its structure, contents and editorial policy. Besides that, this introduction defines the underpinnings of the journal’s regulatory approach. Statutes, administrative regulation and judicial decisions of 2010 pertaining to telecommunications are referred to in detail. It also addresses the main political and juridical discussions on the Brazilian telecommunications sector that took place in the previous year of this journal’s edition.